A banca em Portugal antes e após o efeito subprime - Silva, Luís Miguel Rodrigues (2013)
Banking in Portugal before and after the subprime effect ABSTRACT The crisis in the Subprime segment of the US mortgage market has affected several economic and financial sectors, with a particularly significant impact on credit institutions. The central objective of this dissertation is to evaluate the impact of the subprime crisis on the development of the portuguese banking system. It begins with a brief characterization of this sector during the twentieth century and in the period immediately before the subprime crisis, emphasizing the origin of the internationalization process of the portuguese banking sector, its expansion policy and the role of the deregulation process, after 1984, on the arrival of some spanish institutions. In a second part, the portuguese banking system is analyzed within an adverse macroeconomic context, examining the measures adopted by the portuguese government and by the Bank of Portugal to contain the financial crisis, as well as the major recommendations from Basel III. In global terms, it is concluded that the more representative financial institutions in the portuguese banking system comply with the required capital ratios and liquidity levels, as shown by the available stress tests and other indicators that allow monitoring the evolution in credit risk and the potential need to raise more capital. Keywords: Subprime crisis, Liquidity, Portuguese banking system, Solvability and Stress tests; RESUMO A crise no segmento Subprime do mercado hipotecário norte-americano tem afetado variados sectores económicos e financeiros, sendo o seu impacto particularmente significativo junto das instituições de crédito. Esta dissertação tem como objetivo central avaliar o impacto da crise subprime na evolução do sector bancário português. Começa por uma breve caracterização deste sector durante o século XX e na fase anterior à crise subprime, salientando a origem da internacionalização da banca portuguesa, a sua política expansionista, e o papel que a liberalização regulamentar da banca, após 1984, teve na entrada de algumas instituições espanholas. Numa segunda fase analisa-se o sector bancário português num enquadramento macroeconómico adverso, examinando as medidas tomadas pelo governo português e pelo Banco de Portugal, para conter a crise financeira, assim como as principais propostas de Basileia III. Em termos globais, conclui-se que as instituições financeiras mais representativas do sistema bancário português respeitam os respetivos rácios de capital e níveis de liquidez, como se comprova pelos testes de stress disponíveis e outros indicadores que permitem monitorizar a evolução do risco de solvência e a necessidade de eventuais aumentos de capital. Palavras-chave: Crise subprime, Liquidez, Sector bancário português, Solvabilidade e Testes de Stress.